Effective usage of double-stops technique in cello performance / Muhamad Azim Azlan - Azlan, Muhamad Azim (2022)
Double-stop notes may seems like an easy thing to be played. Even though some of the notation might be easy to play on cello, there is many difficult aspects that need to be look through. For this thesis, the study will be focusing on how to effectively use the double-stops technique in cello performance. There will be two musical pieces that will be focused on. The first piece is J.S Bach Cello Suite no.6 in D Major, Sarabande and the second piece is Saint-Saens Cello Concerto no.l in A minor Op.33. Both pieces contained passages of double-stop notes that need to be play precisely.